Associations of Physical Activity and Sleep Quality With Premenstrual Syndrome Severity Among Female Adolescents in Cimahi, Indonesia - Dedeh Sri Rahayu; Murniati; Halimatusyadiah; Hilda Nurul Afidah (STIKes Budi Luhur Cimahi, 2026)
Premenstrual syndrome (PMS) is common among female adolescents and can interfere with learning, emotional well-being, and daily activities. Physical activity and sleep quality are modifiable lifestyle factors that may be associated with PMS severity. This study aimed to determine the associations between physical activity, sleep quality, and PMS severity among eleventh-grade female students at MAN Kota Cimahi in 2025. A quantitative correlational study with a cross-sectional design was conducted in March 2025. From a population of 205 students, 67 respondents were selected using proportional simple random sampling. Physical activity, sleep quality, and PMS were assessed using the IPAQ-SF, PSQI, and SPAF, respectively. Data were analyzed using Gamma correlation. Most respondents had low physical activity (82.1%), poor sleep quality (79.1%), and moderate PMS (65.7%). Physical activity was strongly and inversely associated with PMS severity (γ = -0.787; p = 0.003), whereas poor sleep quality was strongly and positively associated with PMS severity (γ = 0.738; p = 0.004). Physical activity and sleep quality were significantly associated with PMS severity. Higher physical activity was associated with lower PMS severity, whereas poorer sleep quality was associated with greater PMS severity. These findings support school-based nursing education that promotes regular physical activity, healthy sleep habits, menstrual symptom monitoring, and timely referral for adolescents with disruptive symptoms.